2020
DOI: 10.1371/journal.pmed.1003262
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and pharmacological interventions for posttraumatic stress disorder and comorbid mental health problems following complex traumatic events: Systematic review and component network meta-analysis

Abstract: Background Complex traumatic events associated with armed conflict, forcible displacement, childhood sexual abuse, and domestic violence are increasingly prevalent. People exposed to complex traumatic events are at risk of not only posttraumatic stress disorder (PTSD) but also other mental health comorbidities. Whereas evidence-based psychological and pharmacological treatments are effective for single-event PTSD, it is not known if people who have experienced complex traumatic events can benefit and tolerate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
97
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(137 citation statements)
references
References 170 publications
(218 reference statements)
7
97
0
5
Order By: Relevance
“…Then, we conducted a systematic search in the databases PsycINFO and Medline for the period between 1 January 2013 and 22 September 2020. Finally, we reviewed the relevant meta-analyses on the efficacy of psychological interventions for adult PTSD published since 2013 (Asmundson et al, 2019 ; Barawi, Lewis, Simon, & Bisson, 2020 ; Bisson, van Gelderen, Roberts, & Lewis, 2020 ; Carpenter et al, 2018 ; Cipriani et al, 2018 ; Coventry et al, 2020 ; Cusack et al, 2016 ; Gallegos, Crean, Pigeon, & Heffner, 2017 ; Gerger et al, 2014 ; Grasser & Javanbakht, 2019 ; Hegberg, Hayes, & Hayes, 2019 ; Hopwood & Schutte, 2017 ; Karatzias et al, 2019 ; Khan et al, 2018 ; Kline, Cooper, Rytwinksi, & Feeny, 2018 ; Kuester, Niemeyer, & Knaevelsrud, 2016 ; Lenz, Haktanir, & Callender, 2017 ; Lewis, Roberts, Andrew, Starling, & Bisson, 2020a ; Lewis, Roberts, Bethell, Robertson, & Bisson, 2018 ; Lewis, Roberts, Gibson, & Bisson, 2020b ; Mahoney, Karatzias, & Hutton, 2019 ; Mavranezouli et al, 2020 ; Montero-Marin, Garcia-Campayo, López-Montoyo, Zabaleta-Del-Olmo, & Cuijpers, 2018 ; Morina, Malek, Nickerson, & Bryant, 2017a ; Niles et al, 2018 ; Schwartze, Barkowski, Strauss, Knaevelsrud, & Rosendahl, 2019 ; Springer, Levy, & Tolin, 2018 ; Tran & Gregor, 2016 ; Van Dis et al, 2020 ; Wilson et al, 2018 ). Inclusion criteria for the meta-analysis were: (1) RCT, (2) treatment targets primarily chronic PTSD, (3) participants older than 17 years, (4) at least ten participants per condition at post-assessment, and (5) at least 70% of the sample was diagnosed with PTSD by means of a structured interview (Bisson et al, 2013 ).…”
Section: Methodsmentioning
confidence: 99%
“…Then, we conducted a systematic search in the databases PsycINFO and Medline for the period between 1 January 2013 and 22 September 2020. Finally, we reviewed the relevant meta-analyses on the efficacy of psychological interventions for adult PTSD published since 2013 (Asmundson et al, 2019 ; Barawi, Lewis, Simon, & Bisson, 2020 ; Bisson, van Gelderen, Roberts, & Lewis, 2020 ; Carpenter et al, 2018 ; Cipriani et al, 2018 ; Coventry et al, 2020 ; Cusack et al, 2016 ; Gallegos, Crean, Pigeon, & Heffner, 2017 ; Gerger et al, 2014 ; Grasser & Javanbakht, 2019 ; Hegberg, Hayes, & Hayes, 2019 ; Hopwood & Schutte, 2017 ; Karatzias et al, 2019 ; Khan et al, 2018 ; Kline, Cooper, Rytwinksi, & Feeny, 2018 ; Kuester, Niemeyer, & Knaevelsrud, 2016 ; Lenz, Haktanir, & Callender, 2017 ; Lewis, Roberts, Andrew, Starling, & Bisson, 2020a ; Lewis, Roberts, Bethell, Robertson, & Bisson, 2018 ; Lewis, Roberts, Gibson, & Bisson, 2020b ; Mahoney, Karatzias, & Hutton, 2019 ; Mavranezouli et al, 2020 ; Montero-Marin, Garcia-Campayo, López-Montoyo, Zabaleta-Del-Olmo, & Cuijpers, 2018 ; Morina, Malek, Nickerson, & Bryant, 2017a ; Niles et al, 2018 ; Schwartze, Barkowski, Strauss, Knaevelsrud, & Rosendahl, 2019 ; Springer, Levy, & Tolin, 2018 ; Tran & Gregor, 2016 ; Van Dis et al, 2020 ; Wilson et al, 2018 ). Inclusion criteria for the meta-analysis were: (1) RCT, (2) treatment targets primarily chronic PTSD, (3) participants older than 17 years, (4) at least ten participants per condition at post-assessment, and (5) at least 70% of the sample was diagnosed with PTSD by means of a structured interview (Bisson et al, 2013 ).…”
Section: Methodsmentioning
confidence: 99%
“…Another risk is that, focusing on anxiety provoking details of the traumatic events could be experienced as too burdensome for the participants resulting in avoidance behaviour and higher dropout rates. Previous research however showed that in intensive trauma-focused treatment programs the dropout rate is low (32)(33) or comparable to other treatment conditions (30) and trauma-focused treatments are most effective (29). This study will provide more insight into the added value of parental and systemic component to an intensive trauma treatment and the added value of intensifying treatment.…”
Section: Discussionmentioning
confidence: 75%
“…In contrast to EMDR, TF-CBT is a multicomponent treatment consisting of non-trauma-focused and trauma-focused components. When treating adults with complex trauma, trauma-focused therapies that include cognitive restructuring and imaginal exposure are most effective (29). In line with this research, a Dutch study (30) recently showed that a) exposure therapy is effective in the treatment of adults with complex trauma and b) adding a non-trauma-focused component (affective and interpersonal regulation training) to the exposure therapy did not result in better outcomes.…”
Section: Treatment After Family Violencementioning
confidence: 83%
“…Second, patients with depression and CTEs are often refractory to standard treatments [ 27 , 28 ] and need a differential treatment approach [ 68 , 69 ]. Third, there is a lack of recommendations in current clinical guidelines on the importance of recognizing the interpersonal, social, and emotional consequences of patients with MD and interpersonal adversity [ 70 ]. Fourth, health care teams may need to be trained in the trauma-informed care model [ 71 , 72 ].…”
Section: Discussionmentioning
confidence: 99%